A first study on sperm sexing in water buffalo through magnetic nanoparticles - Syed Murtaza Hassan Andrabi; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Ghulam Muhammad Ali (Revista Científica, 2023)
Gender pre-selection is a genetic tool of economic significance, as it permits animal breeders to produce sex- specific progeny, thereby increasing profitability and genetic gain in the livestock industry. A higher percentage of female calves is preferable for dairy production. In Pakistan, water buffalos are primarily kept for dairy purposes. Therefore, this study was designed to optimize the magnetic nanoparticles (MNPs) based sperm sexing technique in water buffalo. Qualified semen samples from five buffalo bulls were pooled and divided into four aliquots. Each aliquot of 50 million sperm was diluted in 1 mL of modified human tubal fluid (mHTF). Three ali-quots (sexed groups) were incubated with 0.67 ml of negatively charged MNPs suspension. The fourth aliquot was incubated without MNPs (called “control group”). Each tube containing sperm-MNPs suspension was slowly shaken for 5 minutes for uniform mixing. The MNPs were negatively charged and (provided by Clemente Associates Inc, Prescott, Arizona, USA) had a diameter of 50 nanometers. The interaction between the negative charge of MNPs and the Z electrical potential of spermatozoa was different for those spermatozoa carrying an X chromosome (-20 mV) and those carrying a Y chromosome (-16 mV). Therefore, the Y chromosome-bearing spermatozoa remained closer to MNPs. Three sexed groups were exposed to a magnet for 10, 20, and 30 minutes. The control group was exposed to the magnet for 20 minutes. Consequently, in the sexed groups, the Y-bearing sperm-MNP complexes remained attached to the tube’s inner wall due to the magnetic force. In contrast, the X-chromosome spermatozoa remained suspended in the medium. Then, suspended spermatozoa carrying the X chromosome were slowly aspirated. The control group was also aspirated and transferred to a new tube. After aspiration, each group’s progressive motility (PM, %) of spermatozoa was assessed through a computer-assisted sperm analyzer (CASA). After that, spermatozoa were centrifuged at 226 × g for 5 minutes to remove the mHTF, and DNA was extracted. Validation of the sexing technique was done through SYBR® Green Real-Time (RT) PCR using two sets of primers for gender-specific genes, i.e., X-linked proteolipid protein (PLP) and sex-determining region Y protein (SRY). Results revealed that PM was similar (p>0.05) in all groups (ranging from 62 to 65%). The mean fold expression of the PLP gene (X chromosome bearing sperm) was higher (p<0.05) in all sexed groups (average: 15.34-fold = 91.09% X chromosome bearing sperm) as compared to control (1.60- fold). In conclusion, the MNPs-based technique appeared to be an effective method for water buffalo sperm sexing as validated by RT PCR.